Pemanfaatan Limbah Kulit Singkong Sebagai Plastik Ramah Lingkungan Untuk Mengatasi Pencemaran Akibat Plastik Polimer - Naomi Nova Mies; Awin Mulyati (Student Research Journal, 2025)
The problem of environmental pollution due to plastic waste is a global issue that urgently needs to be addressed. This research aims to develop environmentally friendly plastics made from cassava peel waste, which is abundant in Indonesia, especially in the cassava-based food industry. Qualitative methods with an exploratory approach are used to understand the potential utilization of this waste. Data was collected through in-depth interviews with industry players, MSME managers, environmental experts, and field observations. Data analysis was carried out inductively, with data reduction and categorization based on themes. Data validity is maintained through triangulation of sources and methods. The research was conducted in Surabaya over a period of one month. The results show that the use of cassava peel waste supports the principles of sustainability and a circular economy, reducing dependence on chemical polymer-based plastics. The public welcomes this product as an environmentally friendly solution, although price is the main consideration. This research concludes that plastic made from cassava peel can reduce organic waste and open up new business opportunities for MSMEs, with successful implementation requiring technological support and government policies to accelerate implementation.